2022
DOI: 10.3390/nu14071496
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Approach to Understanding the Role of Diet in Cancer-Related Fatigue: Challenges and Future Opportunities

Abstract: Cancer-related fatigue (CRF) is considered one of the most frequent and distressing symptoms for cancer survivors. Despite its high prevalence, factors that predispose, precipitate, and perpetuate CRF are poorly understood. Emerging research focuses on cancer and treatment-related nutritional complications, changes in body composition, and nutritional deficiencies that can compound CRF. Nutritional metabolomics, the novel study of diet-related metabolites in cells, tissues, and biofluids, offers a promising to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…Anxiety, which was supported by research from Australia [75], Netherland [76], and Nigeria [77] was the fourth factor in this study that had a significant association with CRF. This may be the result of biologically related processes; in particular, worry may lead to weariness via dysregulation of the hypothalamic-pituitary-adrenal axis [78]. As a result of internal and external stressors during therapy, the hypothalamic-pituitary-adrenal axis becomes dysregulated, depleting the body's supply of cortisol and impairing its ability to secrete it [79].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety, which was supported by research from Australia [75], Netherland [76], and Nigeria [77] was the fourth factor in this study that had a significant association with CRF. This may be the result of biologically related processes; in particular, worry may lead to weariness via dysregulation of the hypothalamic-pituitary-adrenal axis [78]. As a result of internal and external stressors during therapy, the hypothalamic-pituitary-adrenal axis becomes dysregulated, depleting the body's supply of cortisol and impairing its ability to secrete it [79].…”
Section: Plos Onementioning
confidence: 99%
“…This could be as a result of the pathologic nature of cancer and its treatment, which could result in nutritional issues like altered taste, anorexia, diarrhea, and unintended weight loss that could then weaken the cancer survivor and modify their body composition [81]. Additionally, cancer treatments may worsen already-present symptoms or have unfavorable side effects like taste loss, xerostomia, inadequate nutritional intake, nausea, and vomiting, which can cause involuntary muscular atrophy and weakness and increase fatigue due to altered ATP metabolism [78,82].…”
Section: Plos Onementioning
confidence: 99%
“…Potential challenges, long-term treatment, and repeated hospitalizations severely impact the quality of life, substantial financial burden, and psychological stress [ 2 ]. Studies showed that some dietary supplements, ethnic herbs, and teas are used for tumor prevention and treatment [ 3 , 4 , 5 ]. Some natural products from diets or plants are potential anti-tumor drugs and chemotherapy sensitizers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it seems that exercise alone may not successfully target all aspects of CRF, for example, emotional or cognitive fatigue, may actually hinder participants' engagement in interventions such as exercise 15–17 . Diet and sleep hygiene although have evidence that may impact CRF, there remains a lack of studies that incorporate the role of diet in the direct management of CRF or sleep interventions that improve sleep substantially 18 . This lack of improvement in sleep can directly or indirectly effect CRF, this is known as a phenomena called ‘cluster symptoms’ where more than one symptom cluster together and effect each other positively or negatively, for CRF the symptoms identified include sleep, anxiety and depression 19 .…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 , 17 Diet and sleep hygiene although have evidence that may impact CRF, there remains a lack of studies that incorporate the role of diet in the direct management of CRF or sleep interventions that improve sleep substantially. 18 This lack of improvement in sleep can directly or indirectly effect CRF, this is known as a phenomena called ‘cluster symptoms’ where more than one symptom cluster together and effect each other positively or negatively, for CRF the symptoms identified include sleep, anxiety and depression. 19 The presence of these symptoms can lead to stress which may also lead to a further increase in the cluster symptoms.…”
Section: Introductionmentioning
confidence: 99%